Khombouw Bark Painting (The Potential of Asei Island Craft Arts as a Tourism Attraction of Sentani Lake, Jayapura Regency) - Ilham; M. Zaenul Muttaqin; Akhmad Kadir; Usman Idris; Eka Patmasari (Formosa Journal of Science and Technology, 2022)
This paper focuses on reviewing the potential of the Asei Island community as a tourist attraction in Jayapura Regency, Papua Province. This study utilizes a library approach by conducting text and discourse analysis—data obtained from exploring library materials relevant to the research topic. Data analysis was carried out through several stages; data presentation, data reduction, verification, and conclusion. The results of this study indicate that Asei Besar Island has the potential to be developed as a craft tourism village because it is supported by various recreational facilities in the form of natural beauty and religious, cultural, and historical tourism. Bark painting khombouw can be done by developing community-based craft tourism villages by applying the craft advancement through the tourism model. In developing the craft tourism village of Pulau Asei, it is essential to pay attention to several obstacles the artisans. Such as; the difficulty of obtaining raw material for khombouw bark as a result of illegal logging without replanting. Many imitations made to resemble khombouw are found in the form of screen printing. It is widely circulated in the market and displayed with other typical Papuan souvenirs such as noken, koteka, and various statues, as well as the Covid-19 pandemic, which impacts decreasing income. Nevertheless, the artisans still carry out the painting activity because it has become a tradition and identity of the Asei people, which their ancestors inherited.